Necessary trouble : growing up at midcentury - Faust, Drew Gilpin (New York : Farrar, Straus and Giroux, 2023)
"A privileged white girl in conservative, segregated Virginia was expected to adopt a willful blindness to the inequities of race and the constraints of gender. For Drew Gilpin, the acceptance of both female subordination and racial hierarchy proved intolerable and galvanizing. During the 1960s, Drew forged a path of her own, one that would eventually lead her to become a historian of the very conflicts that were instrumental in shaping the world she grew up in." --
Includes bibliographical references (pages 275-288) and index.
Keywords: Faust, Drew Gilpin -- Childhood and youth; Gilpin family; Bryn Mawr College -- Students -- Biography; Concord Academy (Concord, Mass.) -- Students -- Biography; Civil rights movements -- United States -- History -- 20th century; United States -- Race relations -- 20th century; United States -- Social life and customs -- 1945-1970.; Clarke County (Va.) -- Biography; Biographies